2010
DOI: 10.1038/nm.2266
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-124 promotes microglia quiescence and suppresses EAE by deactivating macrophages via the C/EBP-α–PU.1 pathway

Abstract: MicroRNAs are a family of regulatory molecules involved in many physiological processes, including differentiation and activation of cells of the immune system. We found that brainspecific miR-124 is expressed in microglia but not in peripheral monocytes or macrophages. When overexpressed in macrophages, miR-124 directly inhibited the transcription factor CCAAT/ enhancer-binding protein-α (C/EBP-α) and its downstream target PU.1, resulting in transformation of these cells from an activated phenotype into a qui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

31
691
4
5

Year Published

2011
2011
2015
2015

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 714 publications
(731 citation statements)
references
References 46 publications
(47 reference statements)
31
691
4
5
Order By: Relevance
“…Utilizing a mouse model of multiple sclerosis (MS), experimental autoimmune encephalomyelitis (EAE), they found that at the onset of disease the activated microglial cell population had significantly downregulated microRNA-124 expression [3]. In concordance with this finding, highly activated peripheral macrophages expressed very low levels of microRNA-124.…”
mentioning
confidence: 83%
See 4 more Smart Citations
“…Utilizing a mouse model of multiple sclerosis (MS), experimental autoimmune encephalomyelitis (EAE), they found that at the onset of disease the activated microglial cell population had significantly downregulated microRNA-124 expression [3]. In concordance with this finding, highly activated peripheral macrophages expressed very low levels of microRNA-124.…”
mentioning
confidence: 83%
“…In concordance with this finding, highly activated peripheral macrophages expressed very low levels of microRNA-124. Moreover, microRNA-124 expression was found to be low in prenatal and postnatal microglial cells, which exhibit a quasi-activated state compared to adult microglial cells [3]. Thus, microRNA-124 expression in microglial cells is correlated with microglial cell development and activation status.…”
mentioning
confidence: 93%
See 3 more Smart Citations